Focusing the eyes and recognizing objects: evo-devo and the sensitive period - Finlay, Barbara L (Current opinion in behavioral sciences, 2020)
•Evolution both constrains and optimizes developmental mechanisms, and developmental mechanisms canalize evolution.•Evo-devo thus grounds the study of sensitive periods in cognitive development in a broader context.•How the developing eye uses visual experience to optimize its optics is a well-worked out example of the interaction of development and evolution.•Theories of the development of speech and language, by contrast, have made little use of the evolution of their physical mechanisms.•An evolutionary account of human visual competencies can characterize “object recognition” as a specially-adapted human skill. The study of evolution and development together, ‘evo-devo’, is essential to understand sensitive periods. The combination of phylogenetic history, life history, the biophysics of developing physical substrates, as well as cognitive and neural mechanisms, can distinguish their accidental from essential features. Two examples of research programs concerning sensitive periods, the calibration of eye growth by visual experience versus parameter-setting in early speech and language development are contrasted. The satisfactory resolution produced by the multi-level analysis of eye calibration compared to the enduring controversies generated by the exclusive focus on behavioral and cognitive mechanisms in speech and language research are striking. Evo-devo can also reframe classic subjects. ‘Object recognition’, often assumed to be vision’s central function, in phylogenetic perspective emerges as a specialized human adaptation with an unusual sensitive period. Theory-building must go hand in hand with rich description of the sequences of physical states in full evolutionary context to explain any cognitive capacity constructed by the interaction of organism and environment.